2001
DOI: 10.1002/app.1214
|View full text |Cite
|
Sign up to set email alerts
|

Solvent composition and rheology of starch–DMSO–water solutions

Abstract: ABSTRACT:The rheology of starch-DMSO-water solutions was studied as a function of water content and temperature. A correlation between flow regime, temperature, and water content was presented so as to characterize amylose conformation change in a novel way. Rheological behavior was characterized using an empirical equation to classify fluids under study as Newtonian, pseudoplastic, or dilatant. The temperature effect was analyzed through the determination of the apparent activation energy and preexponential c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 21 publications
1
11
0
1
Order By: Relevance
“…1, all the samples in the shear rate range in question (10 -1000 s À1 ) showed a shear-thinning behavior, and could be considered as pseudo-plastic fluids. This shear-thinning behavior of starch has also been reported in other solvents such as water, DMSO, and NMMO [23][24][25]. From Fig.…”
Section: Rheological Proprieties Of Starch In Zncl 2 Aqueous Solutionsupporting
confidence: 82%
“…1, all the samples in the shear rate range in question (10 -1000 s À1 ) showed a shear-thinning behavior, and could be considered as pseudo-plastic fluids. This shear-thinning behavior of starch has also been reported in other solvents such as water, DMSO, and NMMO [23][24][25]. From Fig.…”
Section: Rheological Proprieties Of Starch In Zncl 2 Aqueous Solutionsupporting
confidence: 82%
“…The values of shear stress τ and shear rate $\dot{\gamma}$ were adjusted to the following empirical equation:23 where η is the Newtonian viscosity coefficient (or zero‐shear‐rate viscosity) and α is a constant related to the type of fluid: Newtonian fluid (α = 0), pseudoplastic fluid (α < 0), and dilatant fluid (α > 0).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, starch is very attractive polymer additive for application to flexible photovoltaic devices. [ 114 ] The authors focused on the influence of starch as a rheological modifier on both the viscosity of the perovskite precursor/DMSO solution and the deposition and crystallization of the perovskite on different flat substrates. The results showed that the starch increased the viscosity of the perovskite precursor solutions, thereby enabling top‐quality perovskite films to be deposited in one step (without toxic solvent dripping); drastically influenced the polycrystal size and morphology by acting as a template for growing the perovskite films; and improved the humidity resistance and bending stress of the resulting perovskite films and solar cells.…”
Section: Properties and Classification Of Psc Polymeric Additivesmentioning
confidence: 99%